2017
DOI: 10.3390/s17092028
|View full text |Cite
|
Sign up to set email alerts
|

Event-Driven Observer-Based Smart-Sensors for Output Feedback Control of Linear Systems

Abstract: This paper deals with a recent design of event-driven observer-based smart sensors for output feedback control of linear systems. We re-design the triggering mechanism proposed in a previously reported system with the implementation of self-sampling data smart sensors; as a result, we improve its performance. Our approach is theoretically supported by using Lyapunov theory and numerically evidenced by controlling the inverted pendulum on the cart mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These devices can make decisions based on the data they obtain through instrumental recording. Smart sensors have been used widely in academia and in research, with applications in the transportation and logistics industry [45], manufacturing [46], security [47], and healthcare [48], among many other examples. Toolmakers use machinery and equipment with smart sensors as well, making this class highly applicable to the sector.…”
Section: Digital Technologies For Product and Service Offeringsmentioning
confidence: 99%
“…These devices can make decisions based on the data they obtain through instrumental recording. Smart sensors have been used widely in academia and in research, with applications in the transportation and logistics industry [45], manufacturing [46], security [47], and healthcare [48], among many other examples. Toolmakers use machinery and equipment with smart sensors as well, making this class highly applicable to the sector.…”
Section: Digital Technologies For Product and Service Offeringsmentioning
confidence: 99%
“…Two different event conditions for fault-tolerant control are studied in [23] in terms of the system state and the system state error, respectively. A great deal of research progress has been made (see [24][25][26][27][28][29][30] and the references therein). It was shown in [31] that the deception attacks are viewed as the most dangerous attack behaviors and, therefore, some solutions against deception attacks have been proposed.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [28] proposed optimal and suboptimal consensus filters with event-triggered communication protocols to achieve energy efficiency via reducing unnecessary interactions among the neighboring sensors. More related studies can be found in recent publications [31,32,33,34,35,36,37,38,39,40,41] and references therein.…”
Section: Introductionmentioning
confidence: 99%